2017
DOI: 10.5751/ace-01042-120213
|View full text |Cite
|
Sign up to set email alerts
|

The effect of industrial noise on owl occupancy in the boreal forest at multiple spatial scales

Abstract: ABSTRACT. Noise in natural environments can mask important acoustic signals used for animal communication. Owls use vocal communication to attract mates and defend territories, and also rely on acoustic cues to locate their prey. Industrial noise has been shown to negatively affect owl hunting success and reduce foraging efficiency by affecting their ability to detect prey, but it is not known if this results in reduced habitat suitability for owls in areas near industrial noise sources. To determine if owls a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Average detection probability of Barred Owls using callbacks and ARU survey methods were similar to studies that reported this parameter (Bailey et al 2009, Kissling et al 2010, Shonfield and Bayne 2017. ARUs had higher average detection probability than callbacks across the survey season; however, ARU samples as defined in this study compiled recordings from three consecutive nights at each site.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Average detection probability of Barred Owls using callbacks and ARU survey methods were similar to studies that reported this parameter (Bailey et al 2009, Kissling et al 2010, Shonfield and Bayne 2017. ARUs had higher average detection probability than callbacks across the survey season; however, ARU samples as defined in this study compiled recordings from three consecutive nights at each site.…”
Section: Discussionsupporting
confidence: 77%
“…As survey sites were obtained from random spatial selection rather than from known cores of owl territories, such as a nest site, we cannot assume that owls consistently remained within the 400 m radius buffer during the survey window. Hence, occupancy results at this scale are best described as probability of "use" rather than occupancy, a recommendation by MacKenzie et al (2006) that several comparable studies have employed (Kissling et al 2010, Shonfield andBayne 2017). Future research that evaluates finescale owl movements using GPS telemetry will provide a more robust evaluation of the influence of the predictors considered in our coarse-scale occupancy analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on nocturnal birds suggest that anthropogenic noise can have little impact on their habitat occupation (Shonfield and Bayne 2017), while others have shown negative impacts on their foraging efficiency (Mason et al 2016;Senzaki et al 2016), decreases of habitat occupation Ciach 2017, 2018), and reduction of their species richness in urban settings (Fröhlich and Ciach 2019). Albeit several species can take advantage of ALAN (e.g., diurnal raptors and waders that can increase their foraging efficiency in light polluted sites; Debrot 2014), it is unclear how ALAN may shape the distribution of nocturnal raptors, as well as its influence on nighttime vocal activity (Gorenzel and Salmon 1995;Longcore and Rich 2004;Canário et al 2012;Gaston and Bennie 2014;Scobie et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We expected to find a positive association between green cover percentage with the presence of the Mottled Owl given the dependence of this species on well-preserved forested areas for breeding and foraging (Gerhardt et al 1994;Menq and Anjos 2015;Holt et al 2019), as well as previous evidence suggesting strong relationships between the quantity of greenspaces with raptors occurrence in urban areas (Dykstra et al 2012;Poppleton 2016). Furthermore, given the pollution status that noise and ALAN represent, we predicted these variables to be negatively related with the occurrence of the Mottled Owl, as they could limit the habitat use of some owl species (Patón et al 2012;Scobie et al 2016;Ciach 2017, 2019;Shonfield and Bayne 2017). We also predicted that the vocal activity of the Mottled Owl would begin earlier in areas with low anthropogenic noise and light pollution levels, based on previous findings suggesting that both sources of pollution can influence the timing of the singing activity of urban diurnal birds (Dominoni et al 2016;Marín-Gómez and MacGregor-Fors 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Development of road networks, which are considered as a main source of anthropogenic noise, could force owls to abandon seemingly suitable habitats (Hindmarch et al 2012 ), which can lead to a decrease in their population density (Silva et al 2012 ). However, when large patches of primary habitats are available in the landscape, the negative effect of noise could be limited due to the presence of less disturbed parts within (Fröhlich and Ciach 2017 , 2018 ; Shonfield and Bayne 2017 ). Despite the high level of noise, reduced availability of habitats, numerous roadkills (Coffin 2007 ), and flushes related with human presence (Hathcock et al 2010 ; Scobie et al 2014 ; Cavalli et al 2016 ), many owl species inhabit highly urbanized areas (Galeotti 1990 ; Rullman and Marzluff 2014 ).…”
Section: Introductionmentioning
confidence: 99%